Meningkatkan Kemampuan Menulis Pantun Siswa Melalui Model Multiliterasi - Resnani, Resnani (Jurnal PGSD, 2021)
This study aims to determine the improvement of students' ability in writing rhymes by applying the multiliterate learning model in Class V SDN 62 Bengkulu City. This research is a Classroom Action Research which is conducted in two cycles, each of which includes: planning, implementing, observing, and reflecting. The subjects in this study were students of SDN 62 Bengkulu City which consisted of 14 female students and 16 male students. The research instruments used were observation sheets and poetry writing test sheets. The data from this study were analyzed using the average value and the percentage of classical learning completeness with the standard conversion formula of 100. The results showed that the average value of the pantun writing test in cycle I was 68.33 with classical learning completeness of 66.66 % ; There was an increase in cycle II with the average score of the rhyme writing test result was 81.66 with classical learning completeness of 83.33 %. Thus, it can be concluded that the application of the multiliterate learning model can improve students' ability to write rhymes in grade V SDN 62 Bengkulu City. It is recommended that Indonesian teachers, especially the material about pantun, apply a multiliterate model in learning to write pantun by paying attention to student involvement in the learning process, and other researchers can also apply it to other subjects.